1987
DOI: 10.1139/v87-074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, 1H, 13C, and 29Si nuclear magnetic resonance spectra and crystal structure of trans-1,4-diphenyldecamethylcyclohexasilane

Abstract: . Can. J. Chem. 65,437 (1987). The coupling reaction between PhMeSiClz and Me,SiClz in the presence of Na/K alloy resulted in a variety of phenylated permethylcyclohexasilanes of which only trans-1 ,4-Ph2MeloSi6 could be obtained in pure form by repeated recrystallizations. It was studied by means of nmr ('H, I3C, and "Si) and X-ray crystallography. The crystals are monoclinic, P2,/c with a = 10.105(6), b = 14.77(1), c = 9.973(6) A, P = 94.08 (5) [Traduit par la revue]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In both structures the cyclohexasilane ring adopts a twist-boat conformation, which is rather unusual, because most cyclohexasilanes studied so far feature a chair conformation of the cyclopolysilane cycle . The geometry around the endocyclic silicon atoms is approximately tetrahedral with Si–Si–Si bond angles close to the respective angles found in other cyclohexasilane structures, ,, although Si(1) exhibits some distortion due to the steric bulk of the attached t -Bu or Ad group.…”
Section: Resultsmentioning
confidence: 77%
“…In both structures the cyclohexasilane ring adopts a twist-boat conformation, which is rather unusual, because most cyclohexasilanes studied so far feature a chair conformation of the cyclopolysilane cycle . The geometry around the endocyclic silicon atoms is approximately tetrahedral with Si–Si–Si bond angles close to the respective angles found in other cyclohexasilane structures, ,, although Si(1) exhibits some distortion due to the steric bulk of the attached t -Bu or Ad group.…”
Section: Resultsmentioning
confidence: 77%
“…Usually, trans -isomers are obtained, as they crystallize much easier. Pure trans -1,4-Ph 2 Si 6 Me 10 can for instance be crystallized from a mixture of many components (in 5% yield) …”
Section: Resultsmentioning
confidence: 99%
“…After workup, 1 H NMR of the product, which was obtained in quantitative yield, showed that it was the cis -isomer that was present in a 2.3-fold excess. Hereto use was made of the 1 H NMR spectrum of trans -1,4-Ph 2 Si 6 Me 10 , of which the identity has previously been established by X-ray diffraction . Thus, in both cases the majority of trans -dichloride is converted into the cis -diaryl-substituted product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure was determined by X-ray structure determination and NMR data. 246 In an investigation by a Chinese group (p-MeC6H4-SiMe)6, (o-MeC6H4SiMe)6, (PhCH2SiMe)6, (PhEtSi)6, and (PhSiCH2CH:CH2)6 were synthesized by the usual dehalogenation of the dichlorides with Li and characterized by NMR, IR, MS, and UV. 171 In presence of a catalytic amount of sodium methoxide, 1,2-dimethoxytetramethyldisilane was converted into cyclic polysilanes (SiMe2)n (n = 5-7).…”
Section: Nmr Investigationsmentioning
confidence: 99%